PEMBERDAYAAN EKONOMI UMAT MELALUI PEMBIAYAAN MIKRO SYARIAH - Sri Deti (el-Jizya: Jurnal Ekonomi Islam, 2017)
Abstract Economic empowerment of the people means developing an economic system of its own people by the people and for the benefit of the people. It also means improving the ability of the people as a whole by developing and mendinamiskan potential. Resource mobilization efforts to develop the economic potential of the people will increase the productivity of the people. Thus, the people or the people with the environment is able to produce and foster participatory added value increase the prosperity and well-being. There are continuous efforts to improve the economy of the people by strengthening the sector of micro, small and medium, both by the government as policy makers, the private sector (financial institutions bank and non-bank) were enough attention to this sector, or direct community is the driving force with the continued proliferation of barns effort. This was driven by the shift in perspective that had been partly the Community as an employee or employees of being an entrepreneur. One way to strengthen the sector of micro, small and medium enterprises is through micro-financing Islamic, microfinance is an activity of business financing in the form of raising funds on the loan for micro (small) run by entrepreneurs are lower middle income people who have income in below average. The magnitude of the potential of Islamic micro finance will encourage a number of Islamic financial institutions to continue to provide financing facilities to the public, so that all walks of life can be easy to develop a business that has been owned, and for those who would set up a new business. Keywords: Economic Empowerment of People, Microfinance Sharia